User-centered built environment for community participation of cultural center in relation to adaptive architecture - Mantaib, Anis Nur Syazwani; Mohd Zaki, Mohd Zikri; Yuhaniz, Mayamin; Abdul Halim Choo, Iryani (Universiti Teknologi MARA, Perak, 2025)
This study explores the integration of adaptive architecture as a strategic framework for designing user-centred built environments. By prioritizing an understanding of the dynamic relationship between users and their surroundings, architects can address the communities’ evolving needs and demands. Adaptive architecture serves as an innovative approach to creating designs that respond to these dynamics, fostering more inclusive and functional spaces. The research highlights the critical importance of preserving intangible cultural heritage. Beyond strengthening local culture and identity, this preservation contributes to tourism development and economic growth, positioning cultural centres as pivotal spaces for community engagement and participation. This study focuses on adaptive architectural strategies within the context of cultural centres, investigating how such approaches can enhance user-centred design. Employing literature reviews, document analysis, and case studies, it examines the theoretical connections between human behaviour and the built environment. By bridging these insights with practical applications, the research aims to guide architects in creating culturally significant, responsive spaces that balance tradition with innovation and sustain community needs into the future.